When Environmental Sustainability Meets Equity Crowdfunding: The Role of Green Ventures in Job Creation - Basnet, Anup; Blomkvist, Magnus; Lazos, Aristogenis (Entrepreneurship Theory and Practice, 2026)
We investigate how environmentally oriented ventures (EOVs) acquire financial resources through equity crowdfunding (ECF) and allocate resources to job creation. Our results suggest that EOVs raise 22.20% to 34.70% more funding and increase headcount by 18.06% to 61.95% relative to non-environmentally oriented ventures. We argue that environmental orientation may increase demand for labor, through the ongoing development of environmental capabilities, and labor supply, by making EOVs more attractive employers. Our evidence is more consistent with a supply explanation as EOVs find it somewhat easier to hire in tight labor markets. Our study highlights how ECF has real-economic impact through job creation. JEL classification: L26, M13, M14, M51